Study and use of rice husk ash as a source of aluminosilicate in refractory coating - Abdullah, M.N. (MDPI AG, 2021)
The utilisation of rice husk ash (RHA) as an aluminosilicate source in fire-resistant coating could reduce environmental pollution and can turn agricultural waste into industrial wealth. The overall objective of this research is to develop a rice-husk-ash-based geopolymer binder (GB) fire-retardant additive (FR) for alkyd paint. Response surface methodology (RSM) was used to design the experiments work, on the ratio of RHA-based GB to alkyd paint. The microstructure behaviour and material characterisation of the coating samples were studied through SEM analysis. The optimal RHA-based GB FR additive was formulated at 50 wt. FR and 82.628 wt. paint. This formulation showed the result of 270 s to reach 200â¦C and 276â¦C temperature at equilibrium for thermal properties. Furthermore, it was observed that the increased contents of RHA showed an increment in terms of the total and open porosities and rough surfaces, in which the number of pores on the coating surface plays an important role in the formation of the intumescent char layer. By developing the optimum RHA-based GB to paint formulation, the coating may potentially improve building fire safety through passive fire protection. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.